√(х-4)=6-х ОДЗ х-4≥0 х≥4 √х -4= 6-х ОДЗ х≥0
6-х≥0 х≤ 6 х≤ 10
√(х-4)²=(6-х)² √х =10-х
х-4=36-12х+х² √х² =(10-х)²
х²-13х+40=0 х=100-20х+х²
D= 169-160=9 х²- 21х+100=0
x₁=(13+3)/2= 8 не подходит ОДЗ D= 441- 400=41
х₂=(13-3)/2= 5 x₁ =(21+√41)/2 не подходит
x₂ =(21-√41)/2
Объяснение:
1) |x-1|=3,4 расскроем модуль двумя разными знаками:
х-1=3,4 x-1=-3,4
x=3,4+1=4,4; x=-3,4+1=-2,4
2) |1-x|=2,4 расскроем модуль двумя разными знаками:
1-х=2,4 1-x=-2,4
x=1-2,4=-1,4 x=1-(-2,4)=1+2,4=3,4
1) x=4,4; x=-3,4;
2) x=-1,4; x=3,4;